2003
DOI: 10.1017/s0020818303574045
|View full text |Cite
|
Sign up to set email alerts
|

International Integration and National Corruption

Abstract: We argue that greater degrees of international integration lead to lower levels of corruption, which we define as the misuse of public office for private gain. We theorize that international factors affect a country's level of corruption through two principal channels. One acts through economic incentives, altering for various actors the costs and benefits of engaging in corrupt acts. The second mode is normative. Prevailing norms in international society delegitimate and stigmatize corruption. Countries that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(110 citation statements)
references
References 33 publications
3
102
0
5
Order By: Relevance
“…As countries integrate economically it is possible that increased trade flows, foreign direct investment or the number of transnational companies mean that good business practices and anti-corruption practices are transmitted to the country, thereby reducing the level of corruption. Sandholtz and Gray (2003) proved the existence of this relationship empirically, and concluded that economic integration would help significantly reduce the level of corruption. This same study showed a positive relationship between the level of corruption in a country and the level of its neighbours.…”
Section: Literature Reviewmentioning
confidence: 90%
See 1 more Smart Citation
“…As countries integrate economically it is possible that increased trade flows, foreign direct investment or the number of transnational companies mean that good business practices and anti-corruption practices are transmitted to the country, thereby reducing the level of corruption. Sandholtz and Gray (2003) proved the existence of this relationship empirically, and concluded that economic integration would help significantly reduce the level of corruption. This same study showed a positive relationship between the level of corruption in a country and the level of its neighbours.…”
Section: Literature Reviewmentioning
confidence: 90%
“…This same study showed a positive relationship between the level of corruption in a country and the level of its neighbours. As in Sandholtz and Gray (2003), Goel and Nelson (2007) found a positive relationship between the level of corruption in neighbouring states and the level of corruption in the state analyzed. The authors use U.S. state level data over the period 1995-2004 to identify the factors that affect the average conviction rate for corruption in the states under study.…”
Section: Literature Reviewmentioning
confidence: 91%
“…In fact, only one of the reporting institutions is based in a non-western culture, specifically Asia. One study asserts that the attempt to understand corruption from the narrow perspective of bribery translates into an attempt to globalize the western definition of corruption (Sandholtz and Gray, 2004). It is understandable that managers of various backgrounds and experiences would define corruption differently and most certainly, might not limit its definition to bribery.…”
Section: Studying Corruptionmentioning
confidence: 99%
“…Even with a clear definition, which would be difficult, if not impossible, the measurement of fraud and corruption is also problematic [5]. Due to the secretive nature of fraud and corruption, it is difficult to police [45]. However, with the development of far more sophisticated measurement strategies now available [18][19] [5], it is possible to put in place risk assessment exercises to reduce the incident of fraud and corruption, which international sporting bodies and individual clubs need to focus on to protect themselves from the range of frauds and corrupt acts that damage the integrity of sport, but also its financial capacity to function [20].…”
Section: Fraud and Corrpution: An International Problemmentioning
confidence: 99%